Penerapan Tindak Pidana Ujaran Kebencian dan Ancaman Terhadap Kebebasan Berbicara - Wulandari, Dini (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Freedom of speech is a human right guaranteed by the Indonesian constitution, as stated in Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Even though it is legally recognized, the implementation of freedom of speech in Indonesia is not free from limitations, especially when it relates to speech. hatred that can damage public order and the reputation of others. As a country of law, Indonesia regulates freedom of expression through various regulations, but this law is often misused to limit critical voices against the government or certain policies. This practice generates controversy, threatens democracy, and hinders the development of healthy public discourse. Cases involving individuals and groups, such as Basuki Tjahaja Purnama and the Saracen group, illustrate the tension between freedom of speech and the protection of individual rights. These restrictions on freedom of speech also have the potential to damage pluralism and freedom of expression, as well as increase the imbalance of power between the government and society. This research examines the implications of restrictions on free speech in Indonesia, highlights existing legal challenges, and urges the need for reform to ensure free speech is maintained as a strong pillar of democracy.